Perancangan Buku Ilustrasi Diet Untuk Penderita Gastritis - Eghi Yulina Anggraeni; Subari Subari; Adita Ayu Kusumasari (MAVIS : Jurnal Desain Komunikasi Visual, 2023)
Gastritis is a disease that occurs because a person consumes alcohol excessively, smokes, abuses drugs, the age factor, and also because of the Helicobacter pylori bacteria. One very important way to do after suffering from this condition is to go on a diet, but not everyone understands about a diet specifically for gastritis sufferers. To overcome this, information that can be conveyed regarding diet for gastritis sufferers is needed in the form of an illustrated book. This design model begins with writing the background of the problem followed by collecting primary and secondary data, then analyzing the data, determining the design concept, and carrying out the design process up to the final design. The methods used to collect field data are interviews, questionnaires, and literature reviews. This design resulted in an illustrated book entitled "Diet for Gastritis Sufferers". The content in this illustrated book will provide information about gastritis and diet as one of the cures for managing your diet. This information will be conveyed in language and illustrations that are easy to understand and interesting to read.